Effective Social Media Communication Strategies to Expand the Market Reach of MSMEs During Ramadan Season - Heryadi, D Yadi; Afiat, Muhammad Nur; Kraugusteeliana, Kraugusteeliana (PT. LITERASI SAINS NUSANTARA, 2024)
Ramadan is not only a spiritual time for Muslims but also a significant economic period, especially for MSMEs. During this holy month, consumer demand increases significantly due to preparations for celebrations and social activities. This research aims to examine effective social media communication strategies to expand the market reach of MSMEs during Ramadan season. The methodology employed in this study is a literature review with a qualitative approach and descriptive analysis. Google Scholar is utilized as the primary data source, covering the years 2014 to 2023. The study findings indicate that in designing effective social media communication strategies to expand the market reach of MSMEs during Ramadan season, several crucial steps should be implemented. These include carefully identifying the target audience to ensure the created content is relevant and engaging to them. Subsequently, focus on producing quality content that aligns with the Ramadan theme, including the use of relevant hashtags to enhance visibility. By implementing these steps, it is expected that MSMEs can achieve greater success in expanding their market reach during Ramadan.